Modelling a Brushless DC Motor Power Source Based Two-Finger Gripper - Safreni Candra Sari (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2009)
In industrial automation system and robotic fields, men use gripper as end manipulator to do simple manipulation tasks as grasping, screwing, pulling, etc. In order to obtain stability in manipulating an object, the gripper has to receive the proper current to produce proper gripper force. Therefore the modelling the gripper, hence, plays an important role. The gripper being modelled has two state: open and close. The finger is open, when finger moves away from each other, and close when the finger moves to each other. Opening the gripper can be done by sending voltage 0 to +5 V to the gripper, and close by sending -5 V to 0 V. The voltage magnitude determines the acceleration of the finger movement, hence, the gripforce is determined by the dynamic of the current sent to the brushless dc motor in the gripper. This paper discuss the modelling process of the gripper. At the end, we will have a mathematical model of the gripper.